Calidad Percibida del Cuidado de Enfermería en Niños/as y Estancia Hospitalaria - Altamirano Cárdenas, Liliana Lissette (2016)
The present investigation descriptive correlacional carried out with the aim to determine the Quality Perceived of the Care of Infirmary according to the perspective of the parents and / or keepers of children hospitalized in the service of Pediatrics of the Hospital Belen of Trujillo. The sample population was constituted by 50 parents and / or keepers which were assembling the criteria of selection. The survey applied to itself professional Scale of care of Kristen Swanson (2000) and the card of compilation of information of hospitable stay. It decided by means of the test of independence of criteria square Chi (x2). Of the discussion of the results they came near to the following results: 70 per cent of the keepers they perceive high quality of elegant nurse. 46 per cent of the children has a hospitable stay between 4 to 7 days and, there exists statistical significant relation between the quality perceived of the elegant nurse and the hospitable stay (p = 0,000 <0,05; respectively). KEYWORDS: Quality of the care of Infirmary and hospitable Stay.